PENGGUNAAN DAN FUNGSI KESENIAN KOMPANG PADA ACARA MENGARAK PENGANTIN DI PASIR PENGARAIAN KABUPATEN ROKAN HULU RIAU - Rizqi, Fajar; Wimbrayardi, Wimbrayardi (SENDRATASIK UNP, 2019)
Abstract This study aims to find and describe the existence of Kompang art in Pasir Pengaraian, Rokan Hulu Regency, Riau, which is seen from its use and function. This research method was qualitative. Techniques of data collection were done by taking: 1) Literature study, 2) Observation, 3) Interview, 4) Documentation. Data analysis was classified according to the focus of the study, after being separated then they were arrangedsystematically. The result shows that in its existence, the Kompang art in Pasir Pengaraian, Rokan Hulu Regency, Riau is used only as a medium to broadcast and spread Islam. However, along with the current development era, this art can beperformed in various events in Pasir Pengaraian, Rokan Hulu, Riau such as in the Prophet's birthday, weddingprocession, shaving (cutting hair on infants) and welcoming grand guests. Based on these uses, Kompang art has five functions for the community of Pasir Pengaraian Rokan Hulu Riau Regency, namely: (1) the function of emotional expression, (2) the function of communication, (3) the function of entertainment, (4) the function of continuity of cultural norms, (5) ) the function of ratification of social institutions. Based on its use and function, it can be seen that there is a high response from the community ofPasir Pengaraian, Rokan HuluRegency towards Kompang art activities in the Pasir Pengaraian, Rokan Hulu Regency, Riau so that its existence is always recognized as traditional art with Islamic nuance as one of the cultural heritages of Islam in the life of the community of Pasir Pengaraian, Rokan Hulu Regency, Riau.Keywords: the use, the function, kompang art, the parade bride event